The Role of Mother Empowerment and Macro-Economic Factors for Child Health: An Evidence from Developing Economies - Soharwardi, Mariam Abbas (International Journal of Child Health and Nutrition, 2020)
Objective: To analyzed the role of maternal empowerment and macro-economic variables in the improvement of child health in developing economies. Methodology: Maternal empowerment has measured through five dimensions: work status, awareness, decision making, self-esteem, and self-confidence. Moreover, countries’ net foods imports, countries as secular or non-secular and region are selected as macro-economic factors. On the other hand, child health has analysed through the anthropometric measure, i.e. stunting. The most recent data sets of Demographic and Health Surveys (DHS) of 38 countries have been used. Data has been analyzed through the use of binary logistic regression and explore the impact of maternal empowerment and macro-economic factors on child health. Results: The results explain the positive impact of mother empowerment in the improvement of child health. Furthermore, net food imports are positively effecting the child’s health. Sub-Saharan Africa and Secular states proved to have negative impacts on child health. Most probably the more empowered mothers are more contributors and implement positive effects on their children’s health. Conclusion: The countries which can fill their food deficiencies through food imports have the probability of improved health for the next generation.